2016
DOI: 10.3109/02770903.2016.1174259
|View full text |Cite
|
Sign up to set email alerts
|

Atopy, but not obesity is associated with asthma severity among children with persistent asthma

Abstract: Background and Objective Obesity is associated with an increased risk of asthma in children. Atopic sensitization is a major risk factor for asthma including severe asthma in children. It is unclear if obesity is associated with worse asthma control or severity in children and how its effects compare to atopy. We sought to examine relationships of weight status and atopy to asthma control and severity among a population of predominantly low income, minority children and adolescents with persistent asthma. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Lu et al report that there was no relation between obesity and worse asthma control or severity in low-income, minority (non-Caucasian) children and adolescents with persistent asthma [40]. Yaşar et al state that no relationship between BMI and asthma control levels could be found [41].…”
Section: Asthma Control and Severitymentioning
confidence: 99%
“…Lu et al report that there was no relation between obesity and worse asthma control or severity in low-income, minority (non-Caucasian) children and adolescents with persistent asthma [40]. Yaşar et al state that no relationship between BMI and asthma control levels could be found [41].…”
Section: Asthma Control and Severitymentioning
confidence: 99%
“…Once asthma occurs, it will bring much inconvenience to the patients’ life and work. Moreover, obesity has not only a greater impact on adults, but also a close correlation with asthma in children . Clinical studies have showed that asthma in children is related to the environment and climate changes, indicating a close correlation with the body system.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent childhood wheezing is associated with atopy, and in turn, atopy is one of the strongest risk factors for later asthma and is related to an increased severity of asthma [32]. Atopic children, especially those with multiple sensitization, with asthma tend to be at higher treatment steps and have decreased lung function and more severe asthma in general [33]. In infants, sensitization to egg and milk typically occurs first, later to be followed by sensitization to other foods and airborne allergens.…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%